2018
DOI: 10.1111/risa.12961
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Risk‐Related News Media Messages in 2016 Coverage of Zika Virus

Abstract: News media plays a large role in the information the public receives during an infectious disease outbreak, and may influence public knowledge and perceptions of risk. This study analyzed and described the content of U.S. news media coverage of Zika virus and Zika response during 2016. A random selection of 800 Zika-related news stories from 25 print and television news sources was analyzed. The study examined 24 different messages that appeared in news media articles and characterized them using theories of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 25 publications
3
28
0
3
Order By: Relevance
“…Samuel et al (2018) reported that despite extensive coverage of Zika by the media, people in New York City had an overall poor understanding of Zika virus symptoms, potential complications, modes of transmission, and guidelines for prevention, and that further intervention is needed to properly educate the public. Likewise, another study noted that 40% of news articles on Zika mentioned negative potential outcomes of Zika infection without mentioning ways to prevent infections [ 43 ]. These studies suggest that, in the least, some media coverage could be improved to better educate the public about Zika prevention.…”
Section: Resultsmentioning
confidence: 99%
“…Samuel et al (2018) reported that despite extensive coverage of Zika by the media, people in New York City had an overall poor understanding of Zika virus symptoms, potential complications, modes of transmission, and guidelines for prevention, and that further intervention is needed to properly educate the public. Likewise, another study noted that 40% of news articles on Zika mentioned negative potential outcomes of Zika infection without mentioning ways to prevent infections [ 43 ]. These studies suggest that, in the least, some media coverage could be improved to better educate the public about Zika prevention.…”
Section: Resultsmentioning
confidence: 99%
“…Yet threat also had no effect on sheltering‐in‐place intentions for chemical releases (Heath, Lee, Palenchar, & Lemon, ), without an obvious temporal association. Positive effects of threat might reflect relative media attention to specific transmission routes, such as mosquitoes (74% of 2016 Zika news stories; Sell et al., ), travel (43% and 30%, depending upon the measure), and sex (31%). Yet threat was positively associated with mosquito control and safe sex intentions, but not travel, for the full sample (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…Few mainland Americans were likely directly exposed to CDC's Zika advice during this period, hence the prospective‐advice emphasis. They might have been exposed to media‐relayed advice by this point in 2017, but 40% of 2016 U.S. news stories mentioned Zika's negative consequences without mentioning protective actions (Sell et al., ).…”
Section: Methodsmentioning
confidence: 99%
“…In the case of Zika, this is an especially interesting phenomenon in the context of the media environment before and after local transmission. Prior to local transmission (Samples 1), message content highlighting factual information about Zika was more frequent compared to after local transmission (Samples 2) (Sell et al., ). Despite this, it appears local transmission was a pivotal event that strengthened the relationship between psychological constructs and knowledge of Zika.…”
Section: Discussionmentioning
confidence: 99%
“…Physical proximity to a health threat like Zika is associated with increased perceived risk and concern (Johnson, ) and the content and frequency of Zika coverage in the United States shifted after local transmission. Specifically, there was a relatively greater emphasis on messages to heighten perceived risk and highlighting factual information about Zika prior to local transmission, and a relatively greater emphasis on governmental efforts to control Zika and the controversies surrounding Zika prevention and response efforts after local transmission (Sell et al., ). As a result of this shift in psychological and media responses following local Zika transmission, it would be important to see whether the associations with Zika knowledge and conspiracy beliefs remain constant or change before and after local transmission.…”
Section: Introductionmentioning
confidence: 99%